Phase-locked subdivision method of digital signal based on FPGA. Issue 1 (1st January 2022) - Hou, Han; Cao, Guohua; Ding, Hongchang; Li, Kun; Wang, Aijia
Abstract: In order to improve the accuracy and real-time performance of the subdivision signal expression result of the photoelectric encoder in the signal dynamic measurement process, a phase-locked subdivision method of digital signal based on FPGA is proposed. The open-loop structure is used to realize the large-range detection of the grating measurement system, and the fractional frequency division method is used to realize the subdivision function of the grating moiré signal. In order to verify the effectiveness of the design, we compare the analog signal subdivision with the traditional digital phase-locked subdivision method. The experimental results show that the digital phase-locked subdivision algorithm designed in this paper can be used in the high-frequency moiré signal frequency and rate of change. The subdivision function is realized under the following conditions, which can be better applied to dynamic measurement occasions.